Superheated Steam Can Rapidly Inactivate Bacteria, But Manual Operation of Commercial Units Resulted in Limited Efficacy During Dry Surface Sanitization - Baker, Jakob; Rana, Yadwinder Singh; Chen, Long; Beary, Maria Amalia; Balasubramaniam, V.M.; Snyder, Abigail B. (Journal of food protection, 2025)
•Temperature decreases >4.5 cm from the impingement limit the radius for sanitation.•Short exposure (10 s) led to high kill (9.6 log) at the impingement point.•Training and experience with a unit significantly increased microbial inactivation.•With training and experience, the highest reduction was 3.56 ± 1.27 log CFU/cm2.•Optimizing steam dispersal and trainings may improve large-surface sanitization. Although bench-scale studies have shown that superheated steam is effective for microbial inactivation on surfaces, commercial systems in the hands of human operators have not been evaluated. The first aim of this study was to characterize the temperature of stainless-steel surfaces treated with a commercial unit. The geometric center of the stainless-steel surface was treated with superheated steam at 400 °C from a fixed position. Surface temperatures exceeded 300 °C at the impingement point during 5 min exposure but decreased as surface thickness and distance increased. Ambient temperature (23.5, 12.8, 4 °C) negatively impacted surface temperatures. Next, we evaluated the thermal inactivation of spot-inoculated Enterococcus faecium NRRL B-2354 on stainless steel surfaces. Inactivation of E. faecium decreased from 9.6 ± 0.1 log CFU/cm2 after 10 s of treatment at the point of impingement to 2.8 ± 0.7 log CFU/cm2 after 10 s of treatment at a distance 4.6 cm away from the impingement point (p < 0.05). Finally, we assessed the effects of training on manual operation by human subjects. Human subjects (N = 24) who completed trainings were asked to treat inoculated stainless-steel surfaces. While training improved manual operation of the unit and microbial inactivation of E. faecium (p < 0.05), the highest average reduction achieved by human subjects was only 3.6 ± 1.3 log CFU/cm2. These findings suggest that the tight radius of high surface temperatures around the nozzle limits the effectiveness of manually operated superheated steam units for microbial inactivation. Thus, equipment design improvements are needed to ensure uniform treatment and adequate surface sanitation.